FDI and long-term economic growth in Russia - Boris Taganov (Russian Presidential Academy of National Economy and Public Administration, 2014)
In this paper we consider relationship between foreign direct investment (as one of the mechanisms of technological development) and long-term economic growth. In the beginning we discuss the role of FDI in the increase of total factor productivity from the viewpoint of endogenous growth theory. We then turn to the comparative analysis of FDI inflow to Russia and other countries broken down by economic industries. We find that Russian industries capable of increasing TFP and positively impacting the long-term economic growth are significantly underinvested relative to other countries. Since, in our opinion, pre-existing sources of Russia's economic growth are almost completely exhausted, we suggest several economic policy measures aimed at attracting FDI in Russia and improve the absorptive capacity of the country. – – ( ) . . . , , , . , , , , .
Keywords: E66; F21; O15; O43; 330; FDI; TFP; economic growth; economic policy; human capital